ANTOCYANES FROM CLITORIA TERNATEA FLOWERS - KRYZHAK, LILIIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper shows the promising feasibility of using the clitoral ternary Clitoria ternatea L. in the food industry. The main color molecules of C. ternatea flowers are various anthocyanins derived from the main classes of dolphinidin, such as ternatine. The blue color of flowers contains anthocyanins, which are widely used as a natural source of food dyes. The main properties of anthocyanins - adaptogenic, antispasmodic, anti-inflammatory and stimulating functions; antiallergic action; bactericidal, choleretic, sedative, hemostatic, antiviral properties; insulin-like, photosensitizing action; reduction of fragility and permeability of capillaries, increase of elasticity of vessels; lowering blood cholesterol; increase visual acuity, normalize intraocular pressure; strengthening the body's immunity and protective functions. Anthocyanin dyes of phenolic nature, which belong to bioflavonoids, occupy a special place among biologically active substances in plant raw materials of the clitoral triad. They determine the color of flowers from blue to blue. These plant pigments - anthocyanins - are well soluble in water. The most important factors on which the stability of anthocyanins depends are enzymes, temperature, oxygen, pH, heavy metal ions, ascorbic acid, light, etc. The intensity and variety of color in food depends on the acid content and pH. The same anthocyanins in an acidic environment give a red color, when the pH is shifted to the alkaline side give a blue or purple color, and in a strongly alkaline environment - green. Anthocyanins of flowers сlitoria ternatea L. can be used as a blue food coloring in acidic and neutral foods, in order to restore and increase the intensity of natural color, coloring colorless products and give them an attractive and marketable appearance.
Keywords: clitoral flowers; biologically active components; anthocyanins; extracts; food dye